Effect of Electro-Acupuncture at ST36 and SP6 on the cAMP -CREB Pathway and mRNA Expression Profile in the Brainstem of Morphine Tolerant Mice - Wang, Qisheng; Qin, Fenfen; Wang, Hui; Yang, Huanya; Liu, Qingyang; Li, Zhonghao; Jiang, Yongwei; Lu, Shengfeng; Wang, Qian; Lu, Zhigang (Frontiers in Neuroscience, 2021)
Undoubtedly, opioid drugs have been the most popular treatment for refractory pain since found, such as morphine. However, tolerance to the analgesic effects caused by repeated use is inevitable, which greatly limits the clinical application of these drugs. Nowadays, it has become the focus of the world that further development of non-opioid-based treatment along with efficient strategies to circumvent opioid tolerance are urgently needed clinically. Fortunately, electro-acupuncture (EA) provides an alternative to pharmaceutic treatment, remaining its potential mechanisms unclear although. This study was aimed to observe the effects of EA on morphine-induced tolerance in mice and discover its underlying mechanism. Tail-flick assay and hot-plate test were conducted to assess the development of tolerance to morphine-induced analgesia effect. As a result of repeated administration scheme (10 mg/kg, twice per day, for 7 days), approximately a 2-fold increase was observed in the effective dose of 50% (ED50) of morphine-induced antinociceptive effect. Interestingly, by EA treatment (2/100Hz, 0.5-1.0-1.5mA, 30min/day for 7 days) at the acupoints Zusanli (ST36) and Sanyinjiao (SP6), morphine ED50 curves was remarkably leftward shifted on day 8. In addition, the RNA sequencing strategy was used to reveal the potential mechanisms. Due to the well described relevance of cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), extracellular regulated protein kinases (ERK), and cAMP response element-binding (CREB) in brainstem (BS) to analgesia tolerance, the cAMP-PKA/ERK-CREB signaling was deeply concerned in this study. Based upon Enzyme-Linked Immunosorbent Assay, the up-regulation of the cAMP level was observed, whereas reversed with EA treatment. Similarly, western blot revealed the phosphorylation levels of PKA, ERK, and CREB were up-regulated in morphine-induced tolerance, whereas the EA group showed a significantly reduced expression level. The present study indicates that the cAMP-PKA/ERK-CREB pathway plays a crucial role in attenuating morphine antinociceptive tolerance by EA and suggests several potential biological targets involved in EA, supporting a useful treatment for combatting the opioid epidemic, and opioid-tolerant patients.